Evaluation of the structures of the optic nerve and chiasm in patients with skull base tumors using high-resolution MRI - Ekaterina S. Egorova; Valeriia V. Musulevska; Mykola O. Guk; Oksana Y. Skobska (Ukrainian Neurosurgical Journal)
Objective: To investigate the effectiveness of radiological methods for diagnosing optic nerve and chiasm atrophy in compressive optic neuropathy caused by tumors of the chiasmal-sellar region (CSR). Material and methods: The diagnostic and treatment outcomes of 50 patients (100 eyes) with CSR tumors were analyzed. These patients were treated at the A.P. Romodanov Institute of Neurosurgery of the National Academy of Medical Sciences of Ukraine from 2021 to 2023. The study group of patients (50 patients) was divided into two subgroups: Group I – restoration of visual functions (26 patients, 52%, 52 eyes); Group II – no restoration of visual functions (24 patients, 48%, 48 eyes). Clinical-neurological, ophthalmological, and otoneurological examinations were performed. MRI of the brain was conducted on all patients using high-field scanners (1.5 and 3.0 Tesla), and measurements of the optic nerve (ON) diameter in the intraorbital and intracranial parts, as well as the height and width of the chiasm. Results: The morphometric parameters of the ON diameter in the intraorbital part and the height of the chiasm did not significantly differ between the studied groups (p>0.05). The morphometric parameters of Group I did not differ from the control group (p>0.05). In Group II the average diameter of the intracranial part of the ON (2.31±0.26 mm) and the average width of the chiasm (11.39±0.31 mm) were statistically significantly different from the control group values: 2.97±0.2 mm and 13.69±0.57 mm, respectively, p<0.05. Despite significant variability in individual characteristics, the parameters of the intracranial part of the ON ≤ 2.31 mm and the chiasm width of ≤ 11.39 mm indicate irreversible atrophic changes and can be used to predict ophthalmological outcomes in patients with CSR tumors. Conclusions: Measuring the thickness of the chiasm and the diameter of the intracranial part of the optic nerve using high-resolution MRI is a convenient and effective method for diagnosing optic nerve atrophy (ONA) and predicting ophthalmological outcomes after decompression of the optochiasmal complex.